Comparison of Stone Scoring Systems as Predictive Tools for Percutaneous Nephrolithotomy Outcome with Anatomical Abnormalities: A Retrospective Study: Comparison of the scoring systems for the Percutaneous Nephrolithotomy - Çil, Gökhan; Yılmaz, Mehmet; Şahin, Yusuf; Müslümanoğlu, Ahmet Yaser (Scripta Medica, 2023)
Background/Aim: European urology guidelines recommend percutaneous nephrolithotomy (PNL) as a treatment modality to remove complex kidney stones over 2 cm in size. Aim of this study was to compare stone scoring systems in predicting stone-free status and complications rate after percutaneous nephrolithotomy (PNL) in abnormal kidneys.Methods: Retrospective analysis of data from 94 patients with anatomical abnormalities who underwent PNL for the kidney stones in the Clinic between January 2017 and January 2022 was performed. Sixty-four patients with renal anomalies who underwent PNL were included in the study. Guy, STONE and CROES nephrolitometry scores were evaluated for each patient by the same researcher using non-contrast computed tomography. The modified Clavien grading system was used to evaluate complications.Results: The mean age and body mass index (BMI) of the patients were 46 ± 11.7 and 28 ± 6 kg/m2, respectively. There was no differences between the groups in terms of operative parameters, renal anomaly categorisation and complications. Compared with the residual stone group, GSS (2.49 vs 3.03; p = 0.001) and STONE scores (7.26 vs 8.38; p = 0.021) in the stone free group were statistically significantly lower, while the CROES score was lower in the group with residual stones (172 vs 245; p < 0.001). In the Chi-square analysis performed between Clavien complication rating and stone scoring systems, no success was found in predicting the presence of complications in any scoring system.Conclusion: Although nomograms were successful in predicting postoperative stone-free status (SFS) after PNL in abnormal kidneys, they may not predict postoperative complications.
Keywords: Renal anomaly; Percutaneous nephrolithotomy; Guy’s score; STONE score; CROES nomogram